STRATEGY STUDY AND DETERMINATION OF ALTERNATIVE RISK-BASED DEVELOPMENT USING PROBLEM NETWORK AND ANALYTIC HIERARCHY PROCESS TO ACCELERATE INVESTMENT IN PLTBM DEVELOPMENT IN INDONESIA - Arifin, Sadiid
The world's fossil fuel reserves are decreasing, but the production and use of fossil fuels in Indonesia continue to increase along with increasing economic development and population growth. Indonesia has committed to maintaining the sustainability of energy use and increasing the use of renewable energy to reduce the impact of climate change. Currently, the transition to renewable energy by utilizing renewable resources continues to be carried out, one of which is through the use of biomass which has a potential of 146.7 million tons. With this great potential, it is hoped that the government can improve energy access to remote areas of the country and increase the renewable energy mix. However, there are obstacles to developing biomass energy investment in Indonesia due to the significant investment risk due to the lack of support for policies and instruments for funding and cooperation. For this reason, this study aims to examine risk-based development strategies to increase investment in PLTBm development in Indonesia. This study uses data sourced from expert interviews and literature studies processed with qualitative thematic analysis, Discourse Network Analysis, SWOT strategy analysis, and Analytic Hierarchy Process. This research will produce alternative PLTBm development schemes by (1) identifying the main risks that hinder investment, (2) formulating strategies to increase investor interest in PLTBm investment (3) formulating alternative development schemes through calculating AHP weights based on existing risks. Thus, it was found that there were risks that hindered investment and strategies to increase investment interest in PLTBm projects.